Acute Urticaria in Inpatients Undergoing Non-emergent Coronary Angiography With Corticosteroid Prophylaxis: A Retrospective Study - Chen, Bangtao; Yu, Fubing; Chen, WenChieh; Wang, Yong; Hao, Fei (Frontiers in Medicine, 2021)
Background and aims: Acute urticaria (AU) is the most frequently reported immediate hypersensitivity reaction in skin by administration of iodinated contrast media (ICM). We aimed to establish the pattern and identify the risk factors of AU among inpatients undergoing non-emergent coronary angiography (CAG) with prophylactic corticosteroids in China. Methods: Medical records of 19326 adult inpatients undergoing non-emergent CAG with prophylactic methylprednisolone in 2013-2019 were retrospectively investigated. AU was identiﬁed within one hour post-ICM administration, and diffuse involvement was defined when wheals occurring in two or more body parts, including back, abdomen, chest, and extremities. 1:4 age- and sex- matched inpatients without AU were randomly selected for assessment of risk factors. Results: Approximately 0.8% of CAG inpatients had AU, including 101 diffuse and 64 limited form. The diffuse AU were more common in settings of non-diagnostic CAG, iohexol used, average ICM injection≥3 mL/min, recurrent CAG and past history of immediate hypersensitivity to ICM. Inpatients with pre-existing allergies, decreased evaluated glomerular filtration rate, increased high sensitivity C reactive protein or neutrophil to lymphocyte ratio prior to CAG had higher probability of AU (odds ratio >1, P <0.05 for all variables). All AU inpatients complained of pruritus and mild itching predominated. AU dissipated in several days under treatment of ebastine or levocetirizine 10mg/daily, but ebastine showed superiority. Conclusions: ICM-induced AU is not uncommon in non-emergent CAG inpatients with prophylactic methylprednisolone. Pre-existing allergies, renal dysfunction or mild inflammation are high-risk factors and antihistamine monotherapy is favorable candidate for ICM-related AU.